Noninvasive ventilation versus oxygen therapy for the treatment of acute respiratory failure. (2nd July 2016) - Pisani, Iara; Comellini, Vittoria; Nava, Stefano
ABSTRACT: Introduction : There is an ongoing discussion on whether oxygen therapy or noninvasive ventilation (NIV) should be used in patient with acute respiratory failure. While respiratory acidosis, especially in case of COPD exacerbation, is a clear indication for NIV, data available in patients with acute hypoxemic respiratory failure (AHRF) are ambiguous. In addition, recently the use of nasal high flow (NHF) has been increased. Despite that NHF has been studied as an alternative to NIV, the clinical advantages of NHF need to be confirmed. Areas covered : The purpose of this review is to enhance our understanding about the management of AHRF in specific settings, focusing on recent papers in which NIV and standard oxygen or NHF have been compared. Expert commentary : The choice of the most appropriate strategy for AHRF treatment should be made based upon patient's clinical status, underlying diseases, level of required respiratory support and patient's tolerance and comfort.